Challenges of citizen education in Mexico, Costa Rica and Peru: an approach from teaching experience - Meléndez Montero, Arturo (2024)
This article presents an analysis of the experiences of three Latin American teachers belonging to Mexico, Costa Rica and Peru, based on the narratives of the subjects, an approach is made to the situation in citizenship education in the region, pointing out the problems and obstacles they present. The formal educational systems and the curricula of the various subjects related to academic citizenship education in Latin American countries when the objective set by the teachers is the formation of active and progressive critical citizenships in response to a context of growing authoritarianism and conservatism by Lastly, it is explained how these obstacles represent challenges that condition but do not fully determine their margin of action in educational spaces, thus highlighting pedagogical work as a possible agent of social transformation.